Supporting business model decisions: a scenario-based simulation approach. (2016) - Täuscher, Karl; Chafac, Melvis
A key challenge for entrepreneurs is to find a robust and scalable business model. In complex environments, business model decisions often build on highly uncertain assumptions. The uncertainty increases when the entrepreneurial venture is confronted with unexpected changes in the environment. This paper proposes an approach to support entrepreneurs in understanding the future implications of their business model decisions. The approach combines system dynamics simulation modelling with formal scenario building. The paper presents a novel conceptual approach to modelling business models. It develops a business model simulation for a multi-sided platform such as the online marketplace eBay. The paper builds future scenarios to conduct simulation experiments that incorporate the uncertainty of developments external to the firm. Based on historic data of eBay, it demonstrates how the scenario-based simulation approach allows comparing the implications of different revenue model options on eBay's performance. Finally, the research discusses the general applicability of the scenario-based simulation approach as a tool for entrepreneurial decision making.